Misdiagnosed outbreak of bartonella bacilliformis in Peruvian Amazon department - Cornejo Tapia, Ángela (2014)
Presentación de Poster realizada durante el "The 16th International Congress on Infectios Diseases ICID". 2-4 April 2014, Cape Town, South Africa